Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content: 1. Content analysis of the book My Beautiful Language for the sixth grade of primary school in light of constructive thinking skills in public schools in The Kingdom of Saudi Arabia Ms. Hessa Jahz Zaben Al-Tarisi, Prof. Abdullah Abdul Khaliq 2. The level of including indicators of sustainable development goals in Omani’s social studies texbooks (5-12) Ms. Najah Salim Al-Habsi, Prof. Ahmed Hamad Al-Rabaani 3. The degree of availability of the principles of the theory of constructivism in the books of health and physical education for the first secondary grade," the track system", from the point of view of health education teachers and supervisors for the secondary stage in Al-Riyadh region Dr. Manal Abduallah Fahad Alqaiawi 4. The Role of Generative Artificial Intelligence in Mathematics Assessment from Teachers’ Perspectives Mr. Abdulrahman Nasser Al-Shahrani 5. A Proposed Program Based on the Japanese Approach to Develop Understanding of Socioscientific Issues and Critical Thinking Skills in Teaching Biology for Secondary School Students Dr. Nasser Qutaym Al-Nufaie 6. Obstacles to the use of social media in teaching Islamic studies in Nigeria from the teachers’ perspective Dr. Aliy Adekunle Abdul-Mutolib ,Prof. Fahd Abdul-Aziz Abanami 7. The degree to which mathematics teachers in Al-Madinah Al-Munawwara practice constructivist theory at the elementary level Mr. Hamza Faisal Alrehaili